2022
DOI: 10.3390/molecules27123902
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Rhodiola rosea L. Preparations in Alleviating Various Aspects of Life-Stress Symptoms and Stress-Induced Conditions—Encouraging Clinical Evidence

Abstract: Rhodiola rosea L. has a long history of use in traditional medicine to stimulate the nervous system, treat stress-induced fatigue and depression, enhance physical performance and work productivity and treat gastrointestinal ailments and impotence. Apart from its well-established traditional use, a significant number of publications on the clinical efficacy of various R. rosea preparations can be found in the literature. The majority of these studies are related to the efficacy of R. rosea in terms of cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 47 publications
1
31
1
1
Order By: Relevance
“…Although most of the studies used a RR supplement that was standardized for a specified concentration of a marker compound, there was variation between the concentrations of the marker compounds used. RR is composed of many different phytochemicals, but it is commonly believed that the therapeutic benefit is derived from the rosavins and salidroside, which occur naturally in a roughly 3:1 ratio (Stojcheva & Quintela, 2022). As a result, the majority of the studies that used a standardized extract were either standardized for 3% rosavins and 1% salidroside (Ballmann et al, 2019; De Bock et al, 2004; Noreen et al, 2013; Williams et al, 2021), or for 3% rosavins only (Jówko et al, 2018; Walker et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Although most of the studies used a RR supplement that was standardized for a specified concentration of a marker compound, there was variation between the concentrations of the marker compounds used. RR is composed of many different phytochemicals, but it is commonly believed that the therapeutic benefit is derived from the rosavins and salidroside, which occur naturally in a roughly 3:1 ratio (Stojcheva & Quintela, 2022). As a result, the majority of the studies that used a standardized extract were either standardized for 3% rosavins and 1% salidroside (Ballmann et al, 2019; De Bock et al, 2004; Noreen et al, 2013; Williams et al, 2021), or for 3% rosavins only (Jówko et al, 2018; Walker et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Within these examinations, elucidation of the mechanisms by which bioactive components of RR exert their physiological effects is also warranted. Importantly, while the focus of the present review was physical performance and related outcomes, it is noteworthy that RR has been investigated for numerous other performance-enhancing effects, notably those related to cognitive function and general well-being (10,11,44,45,46) . While a comprehensive discussion RR's safety profile is beyond the scope of the present review, this botanical was deemed to have 'acceptable safety data' by the World Federation of Societies of Biological Psychiatry and Canadian Network for Mood and Anxiety Treatments Taskforce (47) .…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…17 A 2022 review article examines the effectiveness of rhodiola in stress-induced depression and fatigue as well as its ability to positively affect work productivity and provide anti-inflammatory benefits. 18 A 2017 trial looked at rhodiola's efficacy in treating symptoms of burnout for a period of 12 weeks and found that Rhodiola was effective in alleviating most of the tracked variables in as little as 1 week with continued reduction in these variables over time. 19 Another 2022 placebo-controlled trial, which combined rhodiola with B-vitamins, green tea, and magnesium, found that there was a decrease in perceived stress in both the variable and placebo groups on the DASS-42 stress questionnaire, but that the variable group showed a statistically significant decrease in scores when compared to placebo.…”
Section: The Science and Safety Of Common Botanicals For Stressmentioning
confidence: 99%